THE IMPLEMENTATION OF THE DEATH PENALTY FOR MEMBERS OF THE INDONESIAN NATIONAL POLICE AS NARCOTICS DEALERS - Paulus Bill Regent A; Mada Apriandi Zuhir; Henny Yuningsih (Fakultas Hukum Universitas Sriwijaya, 2026)
Narcotics crime is a serious crime, this is caused by the impact of narcotics circulation on society. The circulation of narcotics is growing both from the method of crime and the type of narcotics. The Narcotics Law applies the death penalty as one of the penalties for drug dealers. This study discusses how the implementation of the death penalty for drug crimes for police members involved as drug dealers Decision No.56 Pid.Sus/2020PN.Dpk, and decision No.227/Pid.Sus/2020 PN. Dum, and How to Regulate the Death Penalty for Drug Dealers in the Future. The research method used is a type of normative research with a statutory, case, conceptual, and analytical approach. The results of this study show in Decision No. 56 / Pid.Sus / 2020PN.Dpk and Decision No. 227 / Pid.Sus / 2020 PN. Dum has been sentenced to death to members of the National Police who lawfully and convincingly distribute narcotics in accordance with the elements of Article 114 paragraph (2) of the Narcotics Law. The panel of judges gave its consideration based on the applicable legal provisions in line with the judge's legal decision theory, namely ratio decidendi and placed the death penalty for the defendant in the decision as nestapa or retribution in accordance with the purpose of retributive crime. The death penalty arrangement for drug dealers in the future, namely removing the death penalty provisions by revising the Criminal Code and the Narcotics Law. In practice, the execution of the death penalty has unfair trial problems, does not eliminate drug crimes, violates human rights and cannot be corrected or changed if there is an error in the verdict if the convict has been executed. This research shows that the main problem in law enforcement of narcotics trafficking is not the severity of sanctions imposed but law enforcement officials.